Principles of Ice Cream Cone Production in an Islamic Economic Perspective in Pacitan Home Industries - Fitrandawati, Erika (Journal of Economics and Social Sciences (JESS), 2024)
Introduction/Main Objectives: This research aims to determine ice cream cones' production and production principles "Proceed Established" Pacitan home industry. Research Methods: The method used in this research is qualitative, data collection is by field research, including interviews, observation, and documentation with business owners and employees of the Pacitan "Proceed Established" ice cream cone production. Finding/Results: The results of this research 1) the production of "Maju Mapan" ice cream cones functions of labor, materials, capital, organization/management, and technology. 2) Based on the production principles applied, they are in understanding with Islamic production principles: creating quality ice cream cones, halal, and tayyib; implementing justice to all employees and meeting consumer demand and satisfaction; not committing acts of exploitation and exploration of existing natural resources; intertwine good relations or ties of friendship between business owners, workers and consumers; free in the use of materials and technology by paying attention to whether it is halal or not violate sharia, and freely manage business income and expenses; Responsible for all production activities which is conducted. Conclusion: Institutions are advised to arrange halal product certification and include production raw materials and expiry dates on the packaging.